Menggapai Kinerja Superior melalui Lean Production - Nur Khusniyah Indrawati (Jurnal Aplikasi Manajemen, 2012)
”Lean Production” has dominated much of the theory and practice of production syatem design since 1980s. It coused by the principles and demonstrated the benefit of ”Lean Production” in industrialized and developed countries. The basic of idea behind the system is eliminating waste. They primary objective of ”Lean Production” is to assist manufacturers who have a desire to improve company’s operations and become more competitive through the implementation or different ”Lean Production” tools and techniques.Keywords: Lean Production, Performance, Waste